PCYT2 overexpression induces mitochondrial damage and promotes apoptosis in hepatocellular carcinoma cells - Xu Bei; Caihong Zhao; Jia Liu; Jun Cao; Wanbao Zheng; Tao Wang; Wenjie Lu; YouZhi Xu (PLoS ONE, 2025)
Phosphatidylethanolamine cytidyltransferase 2 (PCYT2) is commonly regarded as the rate-limiting enzyme in eukaryotic phosphatidylethanolamine synthesis. However, the role of PCYT2 in the development of hepatocellular carcinoma (HCC) unknow. In this study, the role of PCYT2 overexpression in the development of HCC was examined by culturing HepG2 cells. We compared the expression levels of PCYT2 in L02 cells and HepG2 cells. Then, the HepG2 cells were infected with the lentivirus, establishing PCYT2 overexpression cell models. The proliferation, migration, and apoptotic abilities of PCYT2 overexpression in HepG2 cells was observed using western blotting, CCK-8 assay, Transwell assay, wound healing, and plate cloning methods. Based on this overexpression model, we determined the mitochondrial function and lipid content of HepG2 cells using lipidomics. CDP-ethanolamine (CDP-Etn), a downstream product of PCYT2, was added to the HepG2 cells, inhibiting their proliferation and migration. BALB/c female nude mice inoculated with subcutaneously transplanted tumors were used to explore the role of PCYT2. The results of the in-vitro experiments, shown that the expression of PCYT2 in normal hepatocytes was higher than that in HCC cells, and addition of CDP-Etn and PCYT2 overexpression inhibited the proliferation and migration of HCC cells, promoted the apoptosis of HCC cells, and caused mitochondrial damage. The results of in vivo experiments demonstrated that the tumor volume in the PCYT2 overexpression group was significantly smaller than that in the blank control group. Thus, PCYT2 overexpression inhibits the development of HCC, and its mechanism may be related to the impairment of mitochondrial function.